Trends in fatalities due to poisoning at Umtata General Hospital, Mthatha (1993-2005) - Banwari L. Meel (AOSIS, 2009)
Poisoning is a common method of committing suicide in this region of South Africa. Females generally ingest poisons but it is increasingly becoming common in males too. This is a record review of autopsies carried out at the Umtata (Mthatha) General Hospital mortuary, which forms part of the teaching hospital of the Walter Sisulu University Medical School. There were 10 230 unnatural deaths between 1993 and 2005. Of these deaths, 161 (1.6%) were deaths due to poisoning. There was a marked increase in death by poisoning from 2.5% in 1993 to 13.7% in 2004. The highest percentage (17.4%) of poison-related deaths was in 2001, and the lowest (2.5%) was in 1993 and 1994. About two-thirds of victims (66%) were males, and more than half of the victims (51.5%) were in the 11 to 30 age group. There is an increasing trend in fatalities due to poisoning at Umtata General Hospital, Mthatha.